PENGARUH KEPEMIMPINAN, DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN: SURVEI PADA KARYAWAN CV. SURYA PUTRA KIMINDO DI SUKOHARJO - Danisa Putri Pricila; Atik Lusia (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
This study aims to determine whether there is an influence of leadership, work discipline, and compensation on employee performance. The population used in this study were all employees of CV. Surya Putra Kimindo. The sample used was 70 respondents. The type of method used is the quantitative method with the collection technique of Nonprobability Sampling, namely the Saturated Sampling through the distribution of questionnaires. The test analysis used by the researcher is multiple linear regression analysis. The results showed that leadership and work discipline significantly affected employee performance. In contrast, the compensation variable had no significant effect on employee performance. Based on the study's results, CV. Surya Putra Kimindo should further increase the compensation and give it equally to every employee's CV. Surya Putra Kimindo.